ROLE PLAYERS ANALYSIS DALAM KONFLIK PENGELOLAAN SUMBER DAYA ALAM (Studi Kasus Konflik Pertambangan Mangan Di Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur Tahun 2010-2011) - IGNASIUS USBOKO (Program Magister Ilmu Politik, Universitas Diponegoro, 2016)
Manganese mining conflicts in South Central Timor Regency in 2010-2011 is still echoing, especially from the perspective of developmentalism and neoliberalism paradigms. It also can be seen as a paradox of economic development. This study aims to describe and analyze the nature of this conflict in terms of actors, parties, interests, dynamics and its resolutions. By employing Wirawan’s theoretical model of conflict resolutions, this research showed findings as follows: (1) Manganese mining conflicts occurred within six phases, however, the conflict remains unresolved (2) Actors involved are East Nusa Tenggara local government, South Central Timor local government, East Nusa Tenggara Parliament, South Central Timor Parliament, PT SMR, Obama, Landlord. Role in the conflict based on power, interests and goals of the actors (3) Conflict resolution is done by doing the more positive approach of law enforcement through the court process while the use of alternative problem solving only the latent phase and phase triggers. Keywords: Conflict, Conflict Resolutions, Role Players Analysis.